Правова держава: поняття та принципи - Лебедєва, О.В. (Альманах права, 2012)
У статті розглянуто поняття правової держави та її принципів; розкрито відмінності принципів правової держави та соціальної правової держави. В статье рассматривается понятие правового государства и его принципы; раскрыты отличия принципов правового государства и социального правового государства. A significant contribution to the theory of law brought the developers of the concept of separation of powers. It was first promulgated by Aristotle, who saw in the state of three elements: the legislature and the magistracy, the judiciary. The concept of separation of powers began to form in the teachings of John Locke, who singled out the
legislative, executive and federative power. Today, most researchers suggests three main branches of government legislative, executive and judicial branches. First, the term «rule of law» formulated by the German scholar K. Welcker in 1813, and in 1829 his compatriot R. Mole introduced this concept in the legal-political revolution. In Germany, first consider the doctrine of the state of Kant, who applied the concept of «legal law» and the state defined as a combination of many people who are
subject to legal rules, and to the state considered the idea of the rule of law.
The idea of law as a legal construction elaborated science of law in the XVIII — XIX centuries at a time when the constitutional system formed by European countries.
In the early twentieth century. S. Kotlyarevsky said: «The idea of the rule of law came into circulation of the modern civilized society» and «the belief that the state should adopt a legal entity, remains unshakeable.» In modern legal literature, the rule of law is ambiguous, with different accents in its essential characteristics. According to some authors in the rule of law is considered the dominant rule of law, the second — the sovereignty of the people, and others — basic human rights, the fourth — and the power relations on the basis of individual rights. the rule of law, according to Yakovlev — a way of life of the community and its citizens, based on the rule of law, as noted by V.
Nersesyants — the legal form of organization and implementation of the national sovereignty of the people, the opinionof P. Rabinowitz — a state in which the legal means really maximal exercise, safety and protection of fundamental
human rights, in the opinion of Zorkin — the union of power and freedom started from the standpoint of humanism. The famous German Professor K. Hesse identified the following characteristics of law pravoorganizatsiyny forktor State; the rule of law, guarantees the rights and freedoms, the establishment of a fair legal institutions that are
responsible for the proper form of the state; the rule of law must be social.
In the scientific literature, a new generation of the rule of law is ambiguous. From the standpoint of B. Hropanyuka, the rule of law is a form of organization and activity of the government, which is based on the relationship with the individual and their associations on the basis of the law. According to Komarova the rule of law a form of
democracy, citizens’ political organization, which operates on the basis of law, an instrument of protection and the rights, freedoms and responsibilities of each person. N. Vitruk believes that the rule of law is the organization and functioning of the public (political) power, as well as its relationship with the individual, based on the Constitution
and laws in accordance with the requirements of law, the essential of which is the recognition and enforcement of the rights and freedoms of man and citizen. In terms of A. Malko, the rule of law — is an organization of political power, which creates conditions for the fullest support of the rights and freedoms of man and citizen, as well as the
most consistent connection with the rights of state power in order to prevent abuse.
State law currently in force in many constitutions of modern states, including the Constitution of Ukraine, declares as a state social. Some authors argue that the concept of «social state of law» was first used in 1929 by a German jurist H. Heller as
an alternative to the dictatorship of the bourgeoisie and the dictatorship of the proletariat. But the German scholar L. Stein in his «Modern Science and the Future of the legal and state in Germany», emphasized that «the welfare state is designed to always maintain the absolute equality of rights for all social classes, for the individual because of his
power. It must ... promote economic and social advancement of all its citizens, because ultimately, the development of a playing condition of the other, and in this sense refers to the social state». Looking to the foregoing, in our opinion, the social state of law a state that: it provides such a position in society, in which the relationship between classes, nations, and other social groups are not brought to the civil wars, revolutions, social upheavals, social unrest, promotes decent standard of living for all its citizens, takes special care of disadvantaged people (disabled people, pensioners, the sick, etc.) places great emphasis on education, health,human life.